Factors affecting the geographic variability of antibiotic-resistant healthcare-associated infections in the United States using the CDC Antibiotic Resistance Patient Safety Atlas. (12th April 2019) - Kubes, Julianne N.; Fridkin, Scott K.
Abstract: We utilized publicly available data from the Centers for Disease Control to explore possible causes of state-to-state variability in antibiotic-resistant healthcare-associated infections. Outpatient antibiotic prescribing rates of fluoroquinolones and cephalosporins explained some variability in extended-spectrum cephalosporin-resistant Escherichia coli after adjusting for differences in age and healthcare facility composition.